The role of AGG interruptions in fragile X repeat expansions: a twenty-year perspective - Latham, Gary J.; Coppinger, Justine; Hadd, Andrew G.; Nolin, Sarah L. (Frontiers in Genetics, 2014)
In 1994 it was suggested that AGG interruptions affect the stability of the fragile X triplet repeat. Until recently, however, this hypothesis was not explored on a large scale due primarily to the technical difficulty of determining AGG interruption patterns of the two alleles in females. The recent development of a PCR technology that overcomes this difficulty and accurately identifies the number and position of AGGs has led to several studies that examine their influence on repeat stability. Here we present a historical perspective of relevant studies published during the last twenty years on AGG interruptions and examine those recent publications that have refined risk estimates for repeat instability and full mutation expansions.